KRT23 as a Potential Target for Metabolic Dysfunction-Associated Fatty Liver Disease (MAFLD): Evidence From Bioinformatics Analysis, Human Gene Polymorphism and Animal Experiments - Hao Y; Zhang T; Tuerxunmaimaiti S; Tian Y; Wang X; Li Z; Zhao L; Bai L; Chen Q; Li C; Abulitipu A; Wang R; et al. (International Journal of General Medicine)
Yangmin Hao,1,2,* Tao Zhang,3,* Shaliyan Tuerxunmaimaiti,1,2,* Ye Tian,1,4,* Xinyu Wang,1,2 Zhiming Li,5 Liang Zhao,6 Lei Bai,7 Qu Chen,8 Cheng Li,9 Ayiguzhali Abulitipu,1,2,10 Rui Wang,1,11 Sheng Jiang,1,2 Guoli Du1,2,11 1State Key Laboratory of Pathogenesis, Prevention, and Treatment of High Incidence Diseases in Central Asia, Urumqi, Xinjiang, People’s Republic of China; 2Department of Endocrinology, First Affiliated Hospital of Xinjiang Medical University, Urumqi, Xinjiang, People’s Republic of China; 3Department of Human Resources, First Affiliated Hospital of Xinjiang Medical University, Urumqi, Xinjiang, People’s Republic of China; 4Department of Vascular Thyroid Surgery, Digestive Vascular Center, First Affiliated Hospital of Xinjiang Medical University, Urumqi, Xinjiang, People’s Republic of China; 5Department of Ultrasound, First Affiliated Hospital of Xinjiang Medical University, Urumqi, Xinjiang, People’s Republic of China; 6Department of General Medicine (General Surgery), First Affiliated Hospital of Xinjiang Medical University, Urumqi, Xinjiang, People’s Republic of China; 7Department of Hepatobiliary Surgery, First Affiliated Hospital of Xinjiang Medical University, Urumqi, Xinjiang, People’s Republic of China; 8Department of Information Management Section, First Affiliated Hospital of Xinjiang Medical University, Urumqi, Xinjiang, People’s Republic of China; 9Department of Data Statistics and Analysis Center of Operation Management, First Affiliated Hospital of Xinjiang Medical University, Urumqi, Xinjiang, People’s Republic of China; 10Department of General Medicine, Xinjiang Production and Construction Corps Hospital (Second Affiliated Hospital of Shihezi University), Urumqi, Xinjiang, People’s Republic of China; 11Department of Endocrinology, Bayingolin Mongolian Autonomous Prefecture People’s Hospital, Kuerle, Xinjiang, People’s Republic of China*These authors contributed equally to this workCorrespondence: Sheng Jiang; Guoli Du, Email xjjsh@126.com; genemagic@126.comBackground: Metabolic dysfunction-associated fatty liver disease (MAFLD) is highly prevalent in Xinjiang, with genetic factors influencing its pathogenesis. Keratin 23 (KRT23), a liver-enriched protein linked to metabolic regulation, remains understudied in MAFLD genetics.Objective: To investigate associations between KRT23 gene polymorphisms, expression, and MAFLD in Xinjiang.Methods: This study enrolled 1,795 MAFLD patients diagnosed via ultrasonography and metabolic criteria. KRT23 polymorphisms (rs72826004, rs2269859) were analyzed. GEO database screening identified MAFLD-related genes. KRT23 expression was assessed in human serum/liver tissues (ELISA, Western blot, qRT‒PCR, IHC) and murine models (high-fat diet-induced MAFLD and db/db mice).Results: Enrichment analysis identified 10 key MAFLD-associated genes, including KRT23. The rs72826004 TT genotype increased MAFLD risk (OR: 2.156, P=0.007), while rs2269859 TT conferred protection (OR: 0.306, P=0.002). MAFLD patients exhibited elevated KRT23 protein/mRNA levels in serum and liver versus controls. Murine models confirmed higher KRT23 expression in MAFLD and db/db mice compared to wild-type.Conclusion: KRT23 gene polymorphism was associated with the occurrence of MAFLD. The rs72826004 loci TT genotype may be a risk factor for MAFLD, whereas the rs2269859 loci TT genotype may be a protective factor against MAFLD. Higher KRT23 expression (protein and mRNA) is related to MAFLD. KRT23 is a potential target for the treatment of MAFLD.Keywords: metabolic dysfunction-associated fatty liver disease, MAFLD, bioinformatics, gene polymorphism, keratin 23, KRT23, clinical data and animal experiments